An ember in the ashes a novel - Tahir, Sabaa (Razorbill, an imprint of Penguin Random House, 2015)
"Laia is a Scholar living under the iron-fisted rule of the Martial Empire. When her brother is arrested for treason, Laia goes undercover as a slave at the empire's greatest military academy in exchange for assistance from rebel Scholars who claim that they will help to save her brother from execution"...